(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2024)
Introduction: Simple anal fistula can be treated with fistulectomy or fistulotomy. Wound edges marsupialization is a part of treatment. Objectives: To find out the outcomes of the treatment with marsupialization. Methods: Sixty consecutive patients with simple anal ﬁstula were included in this prospective randomized controlled trial study where 30 patients treated with fistulotomy were included group A & 30 patients treated with fistulotomy and marsupialization were included in group B. The primary outcome variable was wound healing time while secondary outcome variables were operating time, postoperative wound size, postoperative pain using visual analogue scale (VAS), post-operative bleeding, wound infection, anal incontinence, recurrence and patient satisfaction. Results: Thirty patients were randomized to group A and 30 to group B. The operating times were significantly different between two groups (21.00±6.35 minutes vs. 28.20±6.57 minutes, P=0.0001) and Postoperative wounds were larger in group A than group B (2.07±0.90 cm2 vs 1.03±0.87 cm2). Bleeding occurred less frequently in group B than group A (10% vs 53.33%, P=0.0003) and wound discharge was observed for a significantly longer duration in group A than group B (4.10±1.8 weeks vs. 2.05±1.71 weeks, P<0.0001). Postoperative wounds in group B healed earlier than group A wounds (3.85±1.19 weeks vs 6.55±1.3 weeks, P<0.0001). VAS scores for postoperative pain on the first postoperative day was (4.05±1.47 vs. 5.15±1.32, P=0.0035) for the two groups. Conclusion: Marsupialization after ﬁstulectomy signiﬁcantly reduces the healing time, the risk of post-operative bleeding and size of the wound without increasing postoperative anal incontinence, recurrence and sepsis. JAFMC Bangladesh. Vol 19, No 1 (June) 2023: 47-49